2019
DOI: 10.4103/ijo.ijo_708_18
|View full text |Cite|
|
Sign up to set email alerts
|

Intravitreal aflibercept injection in Indian eyes with retinopathy of prematurity

Abstract: Purpose: To study the efficacy of intravitreal Aflibercept, an anti Vascular Endothelial Growth factor, (anti-VEGF) in Retinopathy of Prematurity (ROP). Methods: This was a retrospective, interventional consecutive case series of 46 Indian eyes which received intravitreal injection of Aflibercept for High risk Prethreshold ROP, Threshold ROP, and Aggressive-Posterior ROP (AP-ROP). Results: Aflibercept was effective in achieving the primary en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 9 publications
(15 reference statements)
0
20
0
Order By: Relevance
“…Similar to our study, in a series of 46 eyes receiving intravitreal aflibercept monotherapy alone, regression of ROP was seen in 100% of eyes. Although 32.6% (15/46) of eyes reached complete vascularization, incomplete vascularization was persisted in 67.4% of the eyes [18].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Similar to our study, in a series of 46 eyes receiving intravitreal aflibercept monotherapy alone, regression of ROP was seen in 100% of eyes. Although 32.6% (15/46) of eyes reached complete vascularization, incomplete vascularization was persisted in 67.4% of the eyes [18].…”
Section: Discussionmentioning
confidence: 93%
“…Third, the dosing of aflibercept for intravitreal injection in neonates has not been thoroughly tested, and there is some debate about the most effective dose, which necessitates more investigations. Most of the previous studies consider half-dose aflibercept (1 mg/0.025 ml) as a standard dose for intravitreal injection in ROP [18,23]. Recently, Ekinci et al showed that 100% of eyes that had been treated with standard dosage were completely regressed and eyes with a lack of response were present only in the low-dose group (0.4 mg/0.01 ml), although the difference between the groups was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Thirty two of the patients were female. The mean gestational age of the patients included in the study was 26.6 (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33) weeks, and the mean birth weight was 905 (450-1970) grams. The mean postnatal week of the rst intravitreal injection for treatment was 9.1 (4-19) weeks, and the mean follow-up time was 63 (24-250) weeks.…”
Section: Resultsmentioning
confidence: 99%
“…A second injection was applied to 46 eyes of 23 babies 4 weeks after the rst injection. Of these, 38 eyes of 19 infants recovered with re-injection, peripheral retinal vascularization was completed at an average of postnatal week 25.6 ± 4.75 (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36). eight eyes of 4 babies who were re-injected; rescue argon laser photocoagulation therapy was applied approximately 9.2 (7-11) weeks after the start of treatment.…”
Section: Resultsmentioning
confidence: 99%
“…In the article titled “Intravitreal aflibercept injection in Indian eyes with retinopathy of prematurity” published in pages 884-8, issue 6, vol. 67 of Indian Journal of Ophthalmology,[1] the article title incorrectly published as “Intravitreal aflibercept injection in Indian eyes with retinopathy of prematurity” instead of “Intravitreal Aflibercept in Retinopathy of Prematurity: Report no: 1.”…”
mentioning
confidence: 99%